A new disinfectant. Issue 4 (July 1966) - Ross, Philip W.
Abstract : Qualitative and quantitative tests have been carried out to assess the value of Cidex 1, a glutaraldehyde solution, as a disinfectant. Most of the tests were qualitative and were carried out in conditions as closely resembling those found in hospital practice as possible. Recently used anaesthetic equipment, catheters, and a cystoscope, which had been artificially contaminated with suspensions of Staph. aureus, Ps. pyocyanea, and Esch. coli, were used in the tests. The results show Cidex to be a useful disinfectant with a valuable potential in disinfecting hospital articles which, due to their perishable nature or the fragility of component parts, cannot be treated by physical means.